The Impact of Globalization on Higher Education of the 21st Century. Changes in the Social Imaginary of Educational Communities - Acosta Ballestero, Ignacio (2021)
In this paper, a reflexive assessment of the shifts in the social imaginary of the educational communities in higher education of the 21st century generated by the process of globalization in its neoliberal juncture is made. To achieve this endeavour, a contextual discourse analysis about the effects of globalization on international and domestic levels has been carried out in order to deepen on the dynamics and the opportunities to raise awareness of the implications of this type of manifestations. In addition, this analysis aims to take into account the needs of the students of the future generations and works to open the possible scenarios as spaces to transform the teaching and learning process.